Land Snail Community Structure and Diversity in Unprotected and Protected Forest Areas of Ekiti State, Nigeria - Ogbeide, Joshua Osagie; Omogbeme, Moses Ilugbekhai; Uwaifo, Osaretin Peter; Oke, Chris Omamoke (European Scientific Journal, ESJ, 2018)
The community structure and diversity of land snail fauna in Ekiti State was investigated in two protected and one unprotected tropical rainforest ecosystems. Twelve (12) plots measuring 20m x 20m each were surveyed in each forest area, using direct search and leaf-litter filtering techniques. A total of 1095 specimens representing 43 species in 9 molluscan families were collected. Each forest area yielded between 190 and 584 individuals. Alpha diversity ranged from 27 to 32 species, with species richness highest in Ogbesse Forest Reserve and least in the unprotected forest area at Ipole Iloro. The herbivorous Subulinidae and carnivorous Streptaxidae were the most represented families as regards species richness, with family Subulinidae (45.20%) being the most abundant numerically. The most abundant species was Thapsia oscitan of the family Urocyclidae, contributing almost 15% of the total number of individuals. Six (6) species occurred as singleton while 4 species occurred as doubleton. There was considerable variation in species richness between the three sampled forest areas, Cluster analysis formed two groups, Analysis of similarity (ANOSIM) between clusters using the BrayCurtis similarity index gave values of R=1, P=0.34, indicating that the study areas were well separated. The high diversity and abundance recorded from this study reveal the study area is rich in land snails, thus, efforts should be made to maintain the ecological integrity of the protected areas as well as improve biodiversity conservation and management in the unprotected areas.